Police Officers Experience Facing Challenges in Combating Crime in Urban and Rural Areas: A Study on District Police Faridpur (International Journal of Scientific Research and Management (IJSRM), 2024)
Background: The purpose of the study is to find out the challenges police officers face while performing their duties and compare those experiences in different settings. Methods: This study follows the descriptive quantitative approach, where it uses a cross-sectional design. In this study, the data were collected from the police officer by cluster sampling method in District Police Faridpur, Dhaka, Bangladesh. With the help of statistical analysis, the study aims to investigate the nature of the challenges faced by police in combating crime in different settings. Findings: The study explores that getting accurate information about crime is the primary challenge. Along with this, officers face mostly environmental challenges (like cooperation and collaboration) and organizational challenges (lack of resources, workload, stress, hostile environment, and financial worries). In using technology, rural area police face more problems than in urban areas. Finally, it shows that implementing different types of policing strategies can improve the effectiveness of crime in both urban and rural settings. Application/ Improvements: The interested executive bodies can use this information to find out more about the challenges faced by police officers in combating crime.